Hemoptysis due to lung abscess in pediatric patient: Diagnostic approach and treatment - Montolalu, Jewel Patricia; Soehalino, Soehalino; Rafsanjani, Egi Azhar; Setyoningrum, Retno Asih (Edelweiss Applied Science and Technology, 2025)
Hemoptysis in children is a rare and serious clinical symptom often indicative of significant underlying pathology. We report the case of an 11-year-old girl presenting with recurrent hemoptysis caused by a lung abscess. The patient had a history of recurrent respiratory infections and was initially misdiagnosed with pulmonary tuberculosis, leading to an ineffective treatment regimen. Further diagnostic workup, including contrast-enhanced chest CT and microbiological evaluations, revealed a large lung abscess in the left upper lobe, accompanied by anemia of chronic disease and bacterial infection with Micrococcus lylae. Management included a multidisciplinary approach involving intravenous antibiotics, bronchoscopy, and thoracotomy with decortication and abscess drainage. The patient showed significant clinical improvement post-surgery and antibiotic regimen adjustment. This case highlights the importance of accurate diagnosis, the role of advanced imaging, and the integration of medical and surgical interventions in managing hemoptysis due to lung abscesses in pediatric patients. Early recognition and a comprehensive treatment strategy are critical to preventing complications and ensuring optimal outcomes.